A cognição social em musicoterapia: perspectivas sobre a atuação na prática musical interativa em saúde mental - Ivan Moriá Borges Rodrigues (2021)
Many studies that show benefits in communication and social interaction in music therapy for people with schizophrenia, such as those by GERETSEGGER et al (2017) and SILVERMAN (2015), do not refer to the construct of Social Cognition (SC), Neurocognition (NC) and / or its subdomains, which are visibly classified as deficits in schizophrenia, evaluated in other contexts (GREEN, 2007). Recently, the meta-analysis by Jochum van't Hooft et al (2021) identified that the processing of one of the SC subdomains classified as Theory of Mind, and musical perception, may share the same neurobiological circuits, but they do not explore interactive musical practice. , very recurrent in music therapy sessions in Brazil. From the interactive musical practice carried out with patients treated at CERSAM (Reference Center for Mental Health) in Belo Horizonte - MG, it was necessary to investigate and systematically analyze the traces that emerge from the relationship between music therapist and patient in the joint process of music making , and the possible impact of Music Therapy in the care of this population, encompassing psychosocial care and ideals of psychiatric reform with neuroscientific aspects. To develop the research questions, three articles were developed that include an integrative literature review, a description of music therapy care at CERSAM and in mental health services, and a microanalysis relating these traces to social cognition, neurocognition and negative symptoms of schizophrenia. This dissertation contributes to the development of a possible assessment scale on the domains of social cognition and neurocognition in Music Therapy. It was possible to establish a bridge between certain musical situations with these domains, and further theoretical and scientific research is needed to consolidate these relationships.